Vocal Expression Learning based on Self Assessment Major Minor Music Course Malang - Widowati, Rikyan Dyah Bathari; Handayaningrum, Warih; Yermiandhoko, Yoyok (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to (1) describe the process of learning vocal expression through register mastery which takes place in Major Minor Music Course Malang, and (2) testing the effectiveness of the method used in the study, namely Self Assessment. This study uses qualitative methods to describe the learning process of vocal expression through interviews with resource persons, data collection, and observation. The study was conducted over a period of six months to observe, collect data, follow the learning process, and write this.thesisSpoken Voice),Diaphragm Voice,Nasal Voice, andHead Voice. For learning vocal expression, several emotions are classified, namely; (1) sad, spoiled, which gives rise to a nasal, wheezing, and hoarse voice, the result of the Nasal Voice, and vocal fry; (2) angry, excited, irritated, which gives rise to a strong and loud voice, the result of Diaphragm Voice; (3) tense, restless, which tends to bring up the voice / low tone, the result of Chest Voice; and (4) joy, romance, affection, which gives rise to a clear, smooth, and melodious voice, the result of Head Voice.